2022
DOI: 10.1590/acb370405
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the degradation of two bioabsorbable interference screws: an in-vivo study in sheep

Abstract: Purpose: To evaluate in-vivo degradation of two bioabsorbable interference screws. Methods: Twenty-two crossbred Santa Inês ewes were used. A poly-DL-lactide (PDLLA) screw (70%/30%) was inserted in the right pelvic limb, and a PDLLA screw (70%) + β-tri-calcium phosphate (β-TCP) (30%) in the left pelvic limb. Animals were euthanized at one, four, seven and a half and 18 months after surgery.Plain radiography, computed tomography (CT), microCT, and histological analysis were accomplished. Results: PDLLA screw wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Surgery to remove metallic materials can cause tissue trauma because of the need to detach soft tissues [50]. In the present study, we found that, at 28 and 42 days, mineral apposition was stable, and at 42 days, the BIC was greater in both areas (cortical and cancellous areas), in line with previously published studies [51][52][53]. The results demonstrated the stability of the devices in the bone, demonstrating that the fixation device was incorporated.…”
Section: Discussionsupporting
confidence: 91%
“…Surgery to remove metallic materials can cause tissue trauma because of the need to detach soft tissues [50]. In the present study, we found that, at 28 and 42 days, mineral apposition was stable, and at 42 days, the BIC was greater in both areas (cortical and cancellous areas), in line with previously published studies [51][52][53]. The results demonstrated the stability of the devices in the bone, demonstrating that the fixation device was incorporated.…”
Section: Discussionsupporting
confidence: 91%
“…Their ndings indicated 5% of multiloculated pretibial cysts with histiocytic in ltrate around the PLLA debris with surrounding acellular cystic material 2-3 years following implantation 45 . These ndings can appear years following initial implant placement [28][29][30]46 . Drogset et al reported osteolysis around PLLA screws in 16% of ACLR patients 47 .…”
Section: Discussionmentioning
confidence: 99%
“…The "early" shortcomings, experienced around the time of surgery and include intraoperative screw breakage, loss of xation, graft slippage, and screw migration 18,28 . The "late" complications are usually associated with an imbalanced degradation response re ected by in ammatory reactions leading to accelerated or incomplete absorption, joint effusion, bone tunnel widening and encapsulation 18,24,[28][29][30][31] . Additional reported material-related complications are cyst or abscess formation, intraarticular granulomas and adverse foreign body reactions which might result in osteolysis, synovitis and rarely, systematic allergic response 29,32 .…”
Section: Introductionmentioning
confidence: 99%